Influence of Lactobacillus plantarum P-8 on Fermented Milk Flavor and Storage Stability - Dan, Tong; Chen, Haiyan; Li, Ting; Tian, Jiale; Ren, Weiyi; Zhang, Heping; Sun, Tiansong (Frontiers in Microbiology, 2019)
Previously, we demonstrated that the flavor of milk fermented with Lactobacillus delbrueckii subsp. bulgaricus (IMAU20401) and Streptococcus thermophilus (IMAU40133) at a 1:1000 ratio was superior to that of other ratios of the two strains. In this study, Lactobacillus plantarum P-8 was used as the probiotic bacterium. Six ratios (1:1, 1:5, 1:10, 1:50, 1:100, and 1:1000) of L. plantarum P-8 to yogurt starter were evaluated. A total of 66 volatile compounds including aldehydes, ketones, acids, alcohols, esters, alcohols, and aromatic compounds were identified in milk fermented with the six different L. plantarum P-8 to yogurt starter ratios at 0 d of storage. In particular, key flavor compounds, such as 3-methylbutanal, hexanal, (E)-2-octenal, nonanal, 2-heptanone, 2-nonanone and acetoin, were identified in the 1:100 ratio treatment. Furthermore, the viable cell count, pH, titratable acidity, viscosity, and syneresis of the milk samples were analyzed during fermentation and over 14 d of storage at 4ºC. The results indicated that milk can be fermented with L. plantarum P-8 in combination with S. thermophilus and L. delbrueckii subsp. bulgaricus, and the physicochemical characteristics of the milk were not affected by the probiotic bacteria.